VALUE INCREMENT OF MINING COMPANIES THROUGH CORPORATE SUSTAINABILITY AND LEVERAGE - Wibawa, Herry Wira (Journal of Information System, Applied, Management, Accounting and Research; Vol 9 No 1 (2025): JISAMAR (December-February 2025), 2025)
The mining industry plays a strategic role in the Indonesian economy given its significant contribution to state revenues and the provision of essential raw materials for various industrial sectors. Corporate sustainability and leverage are two key factors that are increasingly receiving attention in the literature on finance and strategic management. This research approach is based on the positivist paradigm. Corporate sustainability and leverage act as independent variables, while firm value is the dependent variable. Corporate sustainability has a probability value of 0.00469 <0.05. Leverage has a probability value of 0.0473 <0.05. The F probability test value is 0.001723 <0.05, which means that corporate sustainability and leverage simultaneously affect the value of mining companies. In mining companies, corporate sustainability has a significant impact on firm value, demonstrating high ethical standards, attracting investors, customers, and business partners to social and environmental issues, increasing investor confidence, and improving firm performance. Firm value in the mining industry is influenced by leverage on the ability to generate income to pay debts. Both interact to help companies create a balanced strategy to maximize the value generated by the company .